Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1357/002224087788401115
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of upwelling to mussel production in the rias on the western coast of Spain

Abstract: We have calculated an upwelling index for each month over a 17-year period (1969-1985) for a point off the western coast of Spain. We interpret April through September values of the index to indicate the flux of nitrate-rich water into the Spanish Rias. The index representing the 6-month upwelling series has been correlated with an index representing the conditions of mussels grown during that season on rafts in Ria de Arosa. Two seasons represent extreme upwelling conditions over the 17-year sampling period: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
99
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(107 citation statements)
references
References 1 publication
(1 reference statement)
6
99
1
1
Order By: Relevance
“…Intensive seasonal measurements of primary production within the Iberian upwelling system are yet too scarce to quantify this effect on phytoplankton production. However, such a relationship was implied by the results of Blanton et al (1987), showing that a 2-fold year-to-year variation of the meat quality of harvested m.ussels in the rias could be accounted for by interannual variations in upwelling intensity along the Galician coast. Although several recent studies have pointed to the occurrence of a long-term increase in upwellingfavourable winds in this area (Fraga & Bakun 1993, Binet 1997, Nogueira et al 1997, the wind regime in 1991 could be considered typical for the NW Iberian upwelling system with a mean Iw from April to September (+394 m3 S-' km-') very near the 16 yr average presented by Blanton et al (1987) for the same period of the year from 1969 to 1985 (+379 * 182 m3 S-' km-').…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive seasonal measurements of primary production within the Iberian upwelling system are yet too scarce to quantify this effect on phytoplankton production. However, such a relationship was implied by the results of Blanton et al (1987), showing that a 2-fold year-to-year variation of the meat quality of harvested m.ussels in the rias could be accounted for by interannual variations in upwelling intensity along the Galician coast. Although several recent studies have pointed to the occurrence of a long-term increase in upwellingfavourable winds in this area (Fraga & Bakun 1993, Binet 1997, Nogueira et al 1997, the wind regime in 1991 could be considered typical for the NW Iberian upwelling system with a mean Iw from April to September (+394 m3 S-' km-') very near the 16 yr average presented by Blanton et al (1987) for the same period of the year from 1969 to 1985 (+379 * 182 m3 S-' km-').…”
Section: Discussionmentioning
confidence: 99%
“…The overall control of the hydrodynamic regime on biological activity inside the rias has been particularly well studied with regards to phytoplankton succession (Figueiras & Pazos 1991, Figueiras & Nos 1993, bacterial abundance (Zdanowski & Figueiras 1997), mussel secondary production (Tenore et al 1982, Blanton et al 1987) and certain aspects of biogeochernical cycles in the rias (Prego 1993, 1994, Alvarez-Salgado et al 1996a. On a larger scale, the influence of the high productivity of the Galician Rias extends to the nearby Atlantic shelf, where part of the high biomass produced in the rias is exported and remineralised , Prego & Bao 1997) leaving a distinct signature on the distribution of the chemical (Fraga 1981, Alvarez-Salgado et al 1993 and biological (Estrada 1984) characteristics of the open shelf waters.…”
Section: Introductionmentioning
confidence: 99%
“…The density-driven flow (gravitational convection) is strongly influenced by the freshwater contribution, the wind regime along the main axis of the rías and the upwelling-downwelling events (Blanton et al 1987, Prego & Fraga 1992, Rosón et al 1997 control the water exchange between the rías and the shelf. The Ría de Vigo, the southernmost of the Rías Baixas, is 2160 km 2 in area, 23.3 km 3 in capacity, and averages 221 m depth with a maximum depth of 245 m in the main channel.…”
Section: Methodsmentioning
confidence: 99%
“…Figueiras et al (2002) showed that upwelling/ downwelling dynamics adjacent to the Galician Rías affected phytoplankton biomass and seston quality, which were shown by Fernández-Reiriez et al (1996) to drive mussel growth rates. Blanton et al (1987) had previously shown that upwelling indices (along-shelf winds) off Galicia were linked to mussel condition index, through the linkages with seston. This set of studies, along with ours in Pelorus Sound, are, to our knowledge, the only ones which have demonstrated linkages from climatic variation in physical forcing to formation of seston biomass, through to bivalve aqua culture yield.…”
Section: Forcing Of Seston Biomass and Mussel Aquaculture Yield Withimentioning
confidence: 99%